Genomic epidemiology describes introduction and outbreaks of antifungal drug-resistant Candida auris - Kappel, D; Gifford, H; Brackin, A; Abdolrasouli, A; Eyre, DW; Jeffery, K; Schlenz, S; Aanensen, DM; Brown, CS; Borman, A; Johnson, E; Holmes, A; et al. (Springer Nature [academic journals on nature.com], 2024)
Candida auris is a globally emerged fungal pathogen causing nosocomial invasive infections. Here, we use cutting-edge genomic approaches to elucidate the temporal and geographic epidemiology of drug-resistant C. auris within the UK. We analysed a representative sample of over 200 isolates from multiple UK hospitals to assess the number and timings of C. auris introductions and infer subsequent patterns of inter- and intra-hospital transmission of azole drug-resistant isolates. We identify at least one introduction from Clade I and two from Clade III into the UK, and observe temporal and geographical evidence for multiple transmission events of antifungal drug resistant isolates between hospitals and identified local within-hospital patient-to-patient transmission events. Our study confirms outbreaks of drug-resistant C. auris are linked and that transmission amongst patients occurs, explaining local hospital outbreaks, and demonstrating a need for improved epidemiological surveillance of C. auris to protect patients and healthcare services.